2019
DOI: 10.1080/13647830.2019.1584336
|View full text |Cite
|
Sign up to set email alerts
|

A redox reaction model for self-heating and aging prediction of Al/CuO multilayers

Abstract: Sputter-deposited Al/CuO multilayers capable of highly energetic reactions have been the subject of intense studies for tunable initiation and actuation. Designing high performance Al/CuO-based initiator devices definitively requires reliable prediction of their ignition and reaction kinetics including self-heating or aging as a function of heating rate and environmental conditions. The paper proposes a heterogeneous reaction model integrating an ensemble of basic mechanisms (oxygen diffusion, structural trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…(1 α), limited to independent reactions occurring successively after each other, within specific temperature ranges. However, the thermite reactions, which combines chemical oxido-reduction reactions with mass transport through barrier layers [35][36][37][38] that have dynamical changes in their structures over temperature cannot rigorously be reduced to a single Arrhenius law activation. Thus, we opted for the use of a differential isoconversional method based on the Friedmann method.…”
Section: Thermal Analysis and Kinetic Parameters Of As-prepared Thermite Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1 α), limited to independent reactions occurring successively after each other, within specific temperature ranges. However, the thermite reactions, which combines chemical oxido-reduction reactions with mass transport through barrier layers [35][36][37][38] that have dynamical changes in their structures over temperature cannot rigorously be reduced to a single Arrhenius law activation. Thus, we opted for the use of a differential isoconversional method based on the Friedmann method.…”
Section: Thermal Analysis and Kinetic Parameters Of As-prepared Thermite Materialsmentioning
confidence: 99%
“…Thus, we opted for the use of a differential isoconversional method based on the Friedmann method. [35,[39][40][41] In contrast to Kissinger, this methodology states that the reaction rate is only a function of temperature at constant reaction progress. This can be easily demonstrated by taking the logarithmic derivative of the reaction rate equation (Eq.…”
Section: Thermal Analysis and Kinetic Parameters Of As-prepared Thermite Materialsmentioning
confidence: 99%
“… is the source term representing the exothermal Al oxidation, with corresponding to the value of the redox reaction 2Al + 3CuO → Al 2 O 3 + 3Cu given in [ 28 ]. For more details about the model implementation, see [ 26 ]. Table 1 summarizes the main model parameters used in the following aging study.…”
Section: Methodsmentioning
confidence: 99%
“…Along this line, a very recent and thorough experimental study showed that under slow heating rates, the release of gaseous oxygen from the CuO occurring well below reaction onset (i.e., at ~250 °C) initiates the Al oxidation process at the vicinity of native interfaces until a proper Al 2 O 3 is formed at ~400 °C [ 25 ]. Based on these findings, Lahiner et al proposed a redox reaction model suitable for investigating slow heating rates and low temperature experiments [ 26 ]. The model permits describing the kinetics of the reactant and product layer thicknesses (including Al, CuO, Cu 2 O, Al 2 O 3 ) of reacting sputter-deposited Al/CuO nanolaminates upon annealing at low temperature (ambient to 500 °C) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation